A study on the practice of Organizational Citizenship Behaviour (OCB) in local government: case study in local authorities in Kuching and Samarahan Division / Juana Minit and Bazli Adam Umar Baki - Minit, Juana; Umar Baki, Bazli Adam (2014)
Organizations, whether in public sector or private sector, are now demanding employees who have the traits of "good citizens"-individuals willing to push themselves to assist co-workers and employers at their workplace. In order for these organizations to keep their competitive edge, they need to ensure that their employees are empathic, efficient, and thoughtful of others when executing their functions. By increasing the ability of employees, motivating intrinsically, extending resources and creating favorable environments, Organizational Citizenship Behaviour (OCB) can influence organizational performance. Executing job functions and at the same time performing beyond what is required without expecting to be rewarded is what we refer to in this study as "Organizational Citizenship Behavior" (OCB) (Organ, 1988). In this study, we will try to analyse the level of awareness of OCB among the staff of local authorities in Kuching and Kota Samarahan. With the questions from the questionnaire, we will try to see if they are aware of OCB, what are the factor that influence the OCB and what is the level of practice of OCB. After a thorough analysis of correlation, we will see if there is any significant relationship between these two variables. With the five dimensions of OCB, we are going to measure the level of practice of OCB. The respondents will be asked on how much they have practiced each of the five dimensions. It is hoped that this study will further adds to the volume of study on OCB, since there is a lack of study in this field that focuses on local authorities. By adding more work of research in this field, it is hoped that the literary collection on this work will mature and the society will have deeper understanding on OCB and able to appreciate the knowledge of OCB.